Illumination on the Bamboo Manuscript "Karang Mindu" Collection of Bakhtiar Hanif Kerinci - Azizah, Faras Puji (Journal of Philology and Historical Review, 2023)
The Karang Mindu manuscript is one of the ancient manuscripts originating from Kerinci, one of the collections of Bakhtiar Hanif, which we know that these ancient manuscripts are very important to protect, because they are relics of our ancestors that have high historical value. Not only that, from ancient manuscripts we can find out about the culture of the past about the illumination on the bamboo manuscript "Karang Mindu" collection of Bakhtiar Hanif Kerinci. The purpose of this article is to find out about the manuscript. Overall, the method used in this research is to use a qualitative method using a literature study, by collecting the main source from the EAP Library with documentation number EAP 117/63/1/15, besides that the author also collects sources from various previous studies, books, articles, journals, which are related to the research theme. The result of this research is the content of the manuscript text Karang Mindu explains about a poet whose love is unrequited, besides that there are also interesting illuminations such as Pucuk Rebung, and Keluk Paku. The manuscript motive also describes the life of ancient people who always utilized nature for their needs. Therefore, studying the illuminations in the manuscript helps to strengthen and maintain Kerinci's cultural heritage or local wisdom.